Risk‐reducing surgery in unaffected individuals receiving cancer genetic testing in an integrated health care system. Issue 16 (9th June 2022) - Knerr, Sarah; Guo, Boya; Mittendorf, Kathleen F.; Feigelson, Heather Spencer; Gilmore, Marian J.; Jarvik, Gail P.; Kauffman, Tia L.; Keast, Erin; Lynch, Frances L.; Muessig, Kristin R.; Okuyama, Sonia; Veenstra, David L.; et al.
Abstract : Background: Germline genetic testing enables primary cancer prevention, including through prophylactic surgery. We examined risk‐reducing surgeries in unaffected individuals tested for hereditary cancer susceptibly between 2010 and 2018 in the Kaiser Permanente Northwest health system. Methods: We used an internal genetic testing database to create a cohort of individuals who received tests including one or more high‐penetrance hereditary cancer susceptibility gene. We then identified, after testing, bilateral mastectomy, bilateral salpingo‐oophorectomy (BSO), and total hysterectomy procedures in electronic health record and claims data through 2019. We describe surgery utilization by genetic test results and National Comprehensive Cancer Network (NCCN) guidelines. Results: The cohort included 1020 individuals, 16% with pathogenic/likely pathogenic (P/LP) variants in one or more of the following genes: BRCA1, BRCA2, CHEK2, APC, MUTYH, ATM, MSH2, PALB2, BRIP1, MLH1, MSH6, EPCAM, FLCN, RAD51C, RAD51D, or TP53 . Among individuals with P/LP variants making them candidates for mastectomy, BSO, or hysterectomy per NCCN guidelines, 34% (33/97), 24% (23/94), and 8% (1/12), respectively, underwent surgery during follow‐up. Fifty‐three percent (18/37) of hysterectomies were among APC, BRCA1, and BRCA2 P/LP variant heterozygotes, typically concurrent with BSO. Three individuals with variants of uncertain significance (only) and 22 with negative results had prophylactic surgery after genetic testing. Conclusions: Uptake of risk‐reducing surgery following usual care genetic testing appears to be lower than in studies that actively recruit high‐risk patients and provide testing and follow‐up care in specialized settings. Factors in addition to genetic test results and NCCN guidelines motivate prophylactic surgery use and deserve further study. Abstract : Germline genetic testing enables primary cancer prevention, such as prophylactic surgery. Uptake of risk‐reducing surgery after usual‐care genetic testing appears to be lower than documented in previous studies, which often recruited high‐risk patients and provided testing and follow‐up care in specialized settings.